Creativity, Precarity and Illusio: DIY Cultures and 'Choosing Poverty'. (June 2018) - Threadgold, Steven
Young people investing themselves in DIY cultures have to negotiate the complex but now normalised nexus of employment, unemployment and underemployment to make ends meet, while maintaining space in their lives to pursue their creative and artistic passions. This article presents research with young people in an underground music scene across Australia who are balancing economic pressures with their desires to generate and uphold DIY and punk-influenced activities in a networked community of likeminded friends and collaborators. Many of the participants actively 'choose poverty', that is, they knowingly and strategically make decisions that 'keep overheads low' to free up temporal and mental space to continue to be creative. Their ideas of being successful are not expressed in material terms, but are contingent upon a future where they continue to have the opportunity to invest themselves in their interests even if that means living in relative poverty. Using the oft-ignored Bourdieusian concepts of illusio, struggle and strategy, this article provides a case study of some of the ways young people deal with the risks and opportunities of a precarious existence. In this case, living an ethical life trumps material concerns, projecting a hopeful attitude towards the future.